Stress Analysis on Cracking Plate Structure For Reducing Stress Concentration. Issue 1 (February 2021) - Huda, F; Safrudin, R A; Utomo, S; Rusli, M
Abstract: The structures which are subjected to load experience stress. If there is no discontinuity (defect), the stress is distributed in a particular pattern based on the type of stress. The crack is one defect that is frequently found in the plate structure, which causes stress concentration factor. In this paper, the treatments to reduce concentration factors are applied to plate structures under cracked conditions to investigate the treatment effect to reduce the stress concentration. For that purpose, the low-cost strain indicator using strain gauge integrated with Arduino Uno and computer is constructed to measure the stress distribution on cantilever aluminum plate in the normal conditions, crack, and crack with treatment. The treatments to reduce the stress concentration factor are applied in the form of the stop drill hole and additional hole. The result shows that the given treatment could reduce the stress concentration factor by around 11%. Even though the reduction of the factor was not significant, the treatment could be a fast and straightforward solution in decreasing the stress on the cracking plate structure.